Anxiety following cardiac surgery – an important aspect of health status assessment - Nowicka-Sauer, Katarzyna; Beta, Sebastian; Nowak, Robert; Jarmoszewicz, Krzysztof; Molisz, Andrzej; Batkiewicz, Sebastian; Płotkowska-Baranowska, Agata; Siebert, Janusz (Family Medicine & Primary Care Review, 2016)
Background . Patient-Reported Outcomes (PROs), including psychological factors, have become an important aspect of both health research and clinical practice. Patients who have undergone cardiac surgery can constitute a large subgroup of the patients of a family physician. Postoperative distress has been observed in up to 40% of patients. Objectives. The study aimed to evaluate anxiety levels among patients who had undergone cardiac surgery, and to explore the correlations between anxiety and depression and subjective health status. Material and methods. The research group consisted of 70 patients (48 men, mean age: 65.9 years; ± 8.5). The study was conducted during consultations three months after surgery. The Hospital Anxiety and Depression Scale (HADS), including question regarding suicidal thoughts, was used. A four-point Likert scale was used to evaluate subjective effectiveness of the surgery and the Visual Analogue Scale (VAS) was used to assess subjective health status. Results. An increased level of anxiety was observed in 23 patients (32.9%), and depression was seen in 12 (17.1%). 13 patients (18.6%) indicated that they had had suicidal thoughts. Patients with suicidal ideation had significantly higher level of anxiety. Significant positive correlations were noted between levels of anxiety and depression. Anxiety level correlated negatively with subjective health status and assessment of surgery effectiveness. No significant connections were observed between level of anxiety and sex, age, or the type of surgery. Conclusions . 1. Increased levels of anxiety were observed in a significant percentage of patients who had undergone cardiac surgery. 2. Increased anxiety level is concomitant with depression, suicidal thoughts, and lower subjective health status assessment. 3. Health status assessment following cardiac surgery should also include the evaluation of mental health.